De l’emprise à l’empreinte : cartographier la donnée AIS pour qualifier l’occupation de l’espace maritime caribéen - Iwan Le Berre; Eric Foulquier; Damien Le Guyader; Clément Iphar; Manuel Sahuquet; Pascal Jean Lopez (Cybergeo)
This article introduces the inaugural utilization of an extensive database designed to characterize the presence of merchant ships in the Caribbean maritime region. The occupation of this space by merchant vessels is highly diverse, reflecting a wide range of maritime activities and ship types. To capture the varied geographies that emerge from this diversity, our study employs a detailed analysis facilitated by AIS (Automatic Identification System) data on maritime traffic. Through the development of a comprehensive database that integrates AIS data with ship identification and port terminal profiles, we have conducted an in-depth examination of ship movements throughout an entire year within the Greater Caribbean Region, mapping their primary routes and ports of call. Our findings demonstrate that the spatial footprint of maritime transportation varies according to the type of goods being traded (such as dry or liquid bulk, containers, inter-island cruises and passengers, or service vessels). This database serves as a valuable tool for enhancing our understanding of the environmental impacts associated with different maritime sectors, both at sea, along coastlines, and in port regions, on ecosystems, coastal areas, and local communities.